Diseño de un plan de reabandono de un pozo tipo en el campo La Cira Infantas (2017)
This project sought to design a new methodology of technical re-disposal for wells in the field under study in order to mitigate the current problems and meet the main objective of a technical abandonment of wells. For the proposed, the regulations that govern well abandonment activities, the techniques and operations necessary to design the new methodology of re-use were taken into account. This methodology was implemented in a typical, representative well of the La Cira Infanta Field to validate the design.